Clinical features of respiratory syncytial virus bronchiolitis in an infant: rapid and fatal brain involvement - Paolo Bottino; Rebecca Miglino; Lisa Pastrone; Anna Maria Barbui; Giovanni Botta; Elisa Zanotto; Francesca Sidoti; Cristina Costa; Rossana Cavallo (BMC, 2021)
Abstract Background Respiratory Syncytial Virus (RSV) infection is a significant cause of bronchiolitis and pneumonia, mostly responsible for hospitalization and infant death worldwide. However, in recent years the importance of extrapulmonary RSV manifestations, especially at neurological level, have become evident. Seizures, lethargy, ataxia and status epilepticus are suggestive of brain involvement, but also in their absence a direct neurological damage RSV-related need to be evaluated. Case presentation A 40-day old male infant was admitted to the Emergency Department with severe bronchiolitis and dyspnea. The patient was reported to be coughing for a week with a vomiting episode in the previous two days. The nasopharyngeal swab confirmed the diagnosis of RSV infection and blood gas test showed hypoxemia and respiratory acidosis. For these reasons, the patient was provided with oxygen therapy. A few hours later, after an initial improvement in clinical parameters, a worsening of respiratory dynamics occurred and the patient was prepared for endotracheal intubation, but in the meantime death occurred. During all the observation period in the Emergency Room, no signs of neuropathological damage were evident. Post mortem examination showed lungs congestion with alveolar atelectasis and white matter degradation with severe edema at brain level. Microbiological analysis performed on autoptic samples confirmed the presence of RSV genome in tracheobronchial aspirate, meningeal swabs, pericardic and abdominal fluids, lung and brain biopsies. Conclusions RSV is usually associated with respiratory diseases, however, as reported by an increasingly number of studies, the systemic dissemination of virus during severe disease can lead to a sudden infant death. The clinical picture herein reported showed a severe bronchiolitis resulting in a fatal and underestimated cerebral involvement due to RSV neurotropic behaviour and underline the need for clinicians to pay more attention to neurological involvement of RSV infection, even in absence of cerebral damage evidence.